Singapore-Indonesia ties: renewed deal for a new age - Desker, Barry (2022)
The Singapore-Indonesia Leaders’ Retreat yesterday on Bintan Island produced a significant milestone in ties, taking the bilateral relationship into a new age, says Barry Desker, Singapore’s Ambassador to Indonesia from 1986-1993.